Effect of Dietary Supplementation of Aloe vera Leaves on Growth Performance and Immunity of Fayoumi Chicks - Ahmad Khan, Muhammad Jameel; Khan, Sohail Hassan; Naz, Salma; Gilani, Syeda Surriya; Shafi, Jamila; Hassan, Farooq; Hassan, Mehdi; Anwar, Muhammad (Pakistan Journal of Nutrition, 2014)
A total of 1800 Fayoumi chicks, 28 day-old of age, were used in this study to determine the effects of two levels of Aloe vera leaves on performance and immune parameters. Basal Fayoumi’s diet supplementation with 0, 1.0 or 2.0% Aloe vera leaves was investigated. The chicks were randomly divided into 9 separate floor pens each comprising 200 chicks and three pens (replicates) per treatment group in a completely randomized design. At the end of study, birds fed diets supplemented with 1.0 or 2.0% Aloe vera leaves had greater body weight gain, better feed intake and feed efficiency than those fed diets without Aloe vera leaves. Low morality was recorded in treatment groups. The geometric means HI titres of birds fed on diets containing Aloe vera leaves were higher than those fed on control. Aloe vera leaves included in the Fayoumi’s diet upto 1.0 or 2.0% did not have any deleterious effects on their performance and immunity.